Planning of Enterprise Economic Safety on the Basis of System-Structural Approach - DANILOVA, Elvira I.; MARCHENKO, Valentyna M. (Journal of Advanced Research in Law and Economics, 2019)
The article proposes a methodology for planning economic safety for a company based on the three-level planning of measures to secure the company from a combination of possible threats and risks. Since the main risks of the enterprise arise in the area of resources (derived from all types of resources used by the enterprise), functional (arising in the process of performing functions) and system components (risks of the enterprise as a holistic property complex), it is recommended to plan economic safety at each of the proposed levels, namely: (1) planning of economic safety at the level of the input components of the enterprise; (2) planning of economic safety at the level of the company's functions; (3) planning of economic safety of the enterprise as a holistic management system. On the basis of the analysis of losses from economic activity of industrial enterprises, typical types of threats, which give rise to risks are generalized as a set of internal measures that can be used to prevent future losses; and a system of planned measures for their implementation is proposed. Planning of economic safety in accordance with the proposed systemic-structural approach allows to identify hazards and form directions for evading and reducing of losses as a result of their implementation.